Stress Intensity Factor calculation from displacement fields (Fracture and Structural Integrity, 2017)
In the last two decades, visual image techniques such as Digital Image Correlation (DIC) enabled to experimentally determine the crack tip displacement and strain fields at small scales. The displacements are tracked during loading, and parameters as the Stress Intensity Factor (SIF), opening and closing loads, T-stress can be readily measured. In particular, the SIFs and the T-stress can be obtained by fitting the analytical equation of the Williamstype expansion with the experimentally-determined displacement fields. The results in terms of fracture mechanics parameters strictly depend on the dimension of the area considered around the crack tip in conjunction with the crack length, the maximum SIF (and thus the plastic tip radius), and the number of terms to be considered in the Williams-type expansion. This work focuses in understanding the accuracy of the SIF calculation based on these factors. The study is based on Finite Element Analysis simulations where purely elastic material behavior is considered. The accuracy of the estimation of the SIF is investigated and a guide-line is provided to properly set the DIC measurements. The analysis is then experimentally validated for crack closure measurements adopting the SENT specimen geometry.
Keywords: Stress intensity factor; Digital image correlation; Crack-tip displacement fields